State Plan Proposals 1972-73 Government of West Bengal - Planning Commission (Planning Commission, 1971)
It should be mentioned that the absolute values of the growth rate of workers as worked out from the Census figures of 1961 and 1971 are not dependable, as there was some change in definition between the two Census operations But this methodological factor must have affected all the States more or less in the same manner and the growth rates shown are good enough for comparing one State with another. When it is a question of estimating cultivating land per agricultural worker, the absolute values of growth rates may also be legitimately used, because these carry the necessary correction term with them.
Government of West Bengal Development and Planning Department
Government of West Bengal Development and Planning Department